2006
DOI: 10.1097/01.wnr.0000236853.40221.8e
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid self-administration increases dopamine release in the nucleus accumbens

Abstract: In the present study, dopamine release was monitored during cannabinoid self-administration in rats to achieve a detailed understanding of the way in which dopamine mediates the reinforcing effects of cannabinoids. Extracellular dopamine levels were measured in the shell of the nucleus accumbens of either Lister Hooded or Long Evans rats trained to self-administer the cannabinoid CB1 receptor agonist WIN 55,212-2. A significant relationship between extracellular dopamine levels and bar-pressing rates was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
69
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 23 publications
6
69
0
3
Order By: Relevance
“…Few years ago, by combining intravenous self-administration procedure with in vivo microdialysis technique we measured fluctuations of DA levels in the NAc of rats during voluntary WIN 55,212-2 intake (Fadda et al, 2006). In this study we demonstrated that self-administered doses of intravenous WIN 55,212-2 increase DA release to a similar extent in the NAc shell of Lister Hooded and Long…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…Few years ago, by combining intravenous self-administration procedure with in vivo microdialysis technique we measured fluctuations of DA levels in the NAc of rats during voluntary WIN 55,212-2 intake (Fadda et al, 2006). In this study we demonstrated that self-administered doses of intravenous WIN 55,212-2 increase DA release to a similar extent in the NAc shell of Lister Hooded and Long…”
mentioning
confidence: 62%
“…At preclinical level, it has been now definitely established that cannabinoids act on the brain in a way similar to other drugs of abuse (Gardner, 2002), producing clear subjective effects and leading to drug-seeking and drug-taking behavior (Martellotta et al, 1998;Fattore et al, 2001Fattore et al, , 2007bJustinova et al, 2003Justinova et al, , 2005Spano et al, 2004;Fadda et al, 2006;Deiana et al, 2007). However, the eCB system is not only the primary site of action for the motivational and reinforcing properties of cannabinoids, but it also exerts an overall modulatory effect on brain reward pathways, thus participating in the addictive properties of most drugs of abuse, such as alcohol (Mechoulam and Parker, 2003), nicotine (Viveros et al, 2006;Forget et al, 2006), cocaine (Arnold, 2005), opioids (Navarro et al, 2001;Fattore et al, 2004Fattore et al, , 2005aFattore et al, , 2007dSpano et al, 2007), methamphetamine (MDMA) (Parrott, 2006), and salvinorin (Braida et al, 2007a,b).…”
Section: Cannabinoids and Drug Addictionmentioning
confidence: 99%
See 3 more Smart Citations